Experimental evaluation of heat transfer impacts of tube pitch on highly enhanced surface tube bundle. - Gorgy, Evraam (Kansas State University, 2011)
The current research presents the experimental investigation of the effect of tube pitch on enhanced tube bundles’ performance. The typical application of this research is flooded refrigerant evaporators. Boosting evaporator’s performance through optimizing tube spacing reduces cost and energy consumption. R-134a with the enhanced tube Turbo BII-HP and R-123 with Turbo BII-LP were used in this study. Three tube pitches were tested P/D 1.167, P/D 1.33, and P/D 1.5. Each tube bundle includes 20 tubes (19.05 mm outer diameter and 1 m long each) constructed in four passes. The test facility’s design allows controlling three variables, heat flux, mass flux, and inlet quality. The type of analysis used is local to one location in the bundle. This was accomplished by measuring the water temperature drop in the four passes. The water-side pressure drop is included in the data analysis. A new method called the EBHT (Enthalpy Based Heat Transfer) was introduced, which uses the water-side pressure drop in performing the heat transfer analysis. The input variables ranges are: 15-55 kg/m².s for mass flux, 5-60 kW/m² for heat flux, and 10-70% for inlet quality. The effect of local heat flux, local quality, and mass flux on the local heat transfer coefficient was investigated. The comparison between the bundle performance and single tube performance was included in the results of each tube bundle. The smallest tube pitch has the lowest performance in both refrigerants, with a significantly lower performance in the case of R-134a. However, the two bigger tube pitches have very similar performance at low heat flux. Moreover, the largest tube pitch performance approaches that of the single tube at medium and high heat fluxes. For the R-123 study, the smallest tube bundle experienced quick decease in performance at high qualities, exhibiting tube enhancement dry-out at certain flow rates and high qualities. The flow pattern effect was demonstrated by the dry-out phenomena. At medium and high heat fluxes, as the tube pitch increases, the performance approaches that of the single tube. All tube bundles experience quick decrease in performance at high qualities. Evidently, P/D 1.33 is the optimum tube pitch for the studied refrigerants and enhanced tubes combinations.
Keywords: Convective boiling; Pool boiling; Enhanced tube bundle; Tube pitch; Flooded refrigerant evaporator; The enthalpy based heat transfer analysis (EBHT); Mechanical Engineering (0548)